Fe-OMS-2-coated SiO2 core-shell catalyst for low-temperature synergetic denitration and demercuration and preparation method of Fe-OMS-2-coated SiO2 core-shell catalyst

Through the preparation of Fe-OMS-2@SiO2 core-shell catalyst, citric acid etching, hydrothermal synthesis, sodium borohydride reduction and SiO2 shell coating technology, the problem of NOx and Hg0 removal at low temperature was solved, and high efficiency was achieved , stable and economic catalytic effects.

CN119455974APending Publication Date: 2025-02-18XIANGTAN UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411603708.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove NOx and Hg0 in steel sintered flue gas under low temperature conditions. Traditional catalysts lack reduction performance at low temperatures and their stability needs to be further improved.

Method used

Fe-OMS-2@SiO2 core-shell catalyst is used, which is prepared by citric acid etching, hydrothermal synthesis, sodium borohydride reduction and SiO2 shell coating technology to form rich pore structure and optimize surface chemistry.

Benefits of technology

Realizing efficient NO selective catalytic reduction and Hg0 catalytic oxidation under low temperature conditions, improving the stability and economy of the catalyst and is suitable for steel sintered flue gas treatment in non-electric industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455974A_ABST
    Figure CN119455974A_ABST
Patent Text Reader

Abstract

The invention discloses a Fe-OMS-2 (at) SiO2 core-shell catalyst for low-temperature collaborative denitration and demercuration and a preparation method thereof. The catalyst is a composite material of a Fe-OMS-2 core and a silicon dioxide shell layer, wherein the Fe-OMS-2 core is formed by modifying natural manganese potassium ore (OMS-2) with transition metal iron oxide. The catalyst is specifically prepared from the following components in percentage by mass: 9 percent to 20 percent of Fe2O3, 12 percent to 28 percent of SiO2 and the balance of OMS-2. The preparation method comprises the following steps: by taking a Fe (NO3) 3.9 H2O solution as a precursor solution and tetraethoxysilane as a silicon source, carrying out citric acid etching, hydrothermal reaction and sodium borohydride reduction to prepare a Fe-OMS-2 core, then adopting an active agent CTAB (Cetyltrimethyl Ammonium Bromide) to assist in stirring and dipping to coat Fe-OMS-2 with silicon dioxide, and carrying out centrifuging, drying and calcining to prepare the catalyst. The catalyst is of a blocky structure formed by adhesion of nanorods, silicon dioxide microspheres are evenly attached to the surface of the catalyst, and the catalyst has more active sites and good oxidation-reduction performance; the structure of the catalyst is more stable due to the coating of the silicon shell, the catalyst is protected from being corroded by sulfur oxides, and NO and Hg0 can be efficiently and synergistically removed under a low-temperature condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of environmental catalysis technology, and specifically to a Fe-OMS-2@SiO2 catalyst having both high-efficiency low-temperature denitrification and mercury removal capabilities. 2 Core-shell catalyst and its unique preparation method. Background Art

[0002] The steel sintering process, as a key link in steel production, contains a large amount of nitrogen oxides (NO x ) and mercury (Hg) and other harmful substances have become an environmental problem that needs to be solved urgently. x It not only causes air pollution such as photochemical smog and acid rain, but also poses a threat to human health. 0 Due to its high volatility, toxicity, persistence and bioaccumulation, it can migrate across regions and even around the world, posing long-term hazards to the environment and human health. Therefore, the development of efficient denitrification and demercuration catalysts is of great practical significance. 3 Selective catalytic reduction (NH 3 -SCR) technology is the most widely used flue gas denitrification technology. The SCR denitrification catalyst used in it can promote Hg 0 Oxidation to Hg 2+ The generated Hg 2+ It can be removed by the subsequent wet flue gas desulfurization device (WFGD) to achieve Hg removal. However, the sintering flue gas temperature is low (80-180°C), and the most widely used V 2 O 5 -WO 3 (MoO 3 ) / TiO 2 Commercial catalysts are difficult to directly apply to sintering flue gas. Therefore, the development of high-conversion, environmentally friendly, low-temperature denitrification catalysts to synergistically control NO and Hg has become an urgent problem to be solved.

[0003] As a multivalent active metal oxide, manganese-based catalysts have attracted extensive attention from researchers due to their excellent low-temperature catalytic performance. The secondary oxidation zone of manganese ore is rich in natural cryptomelane (OMS-2), namely cryptomanganese-type oxide (α-MnO 2 Natural cryptomelane (OMS-2) is MnO 2 The allotrope is composed of manganese oxygen octahedron (MnO 6) units are constructed by a 2×2 tunnel structure with a common corner connection method. It has mixed-valence manganese ions, which makes the catalyst have strong redox ability, and is cheap and environmentally friendly. It shows catalytic performance comparable to that of manganese-based catalysts and has become a very promising SCR low-temperature catalyst. However, due to its low specific surface area, natural cryptomelane has the problem of insufficient exposure of active sites, which is not conducive to the catalytic reaction.

[0004] During the preparation of the catalyst, an appropriate amount of acidification treatment can dissolve some of the substances on the surface of the catalyst, thereby forming micropores, grooves and other structures on the surface of the material. These structures not only increase the specific surface area of ​​the catalyst, but also expose the active sites that were originally covered or buried. In many research fields, acid etching modification has been widely used in the preparation of catalysts. For example, acid etching has been proven to be an effective means in the modification process of materials such as natural zeolite and OMS-2. Through acid etching, the specific surface area of ​​these materials can be significantly increased, and the position, amount and proportion of the acid center on the surface can be changed, thereby improving their catalytic activity. As a highly efficient catalyst material, the physical and chemical properties of OMS-2 have an important influence on the catalytic activity. By doping with different metal elements, the catalytic performance of OMS-2 can be significantly adjusted. In recent years, FeO x Due to its low cost, strong oxygen carrying capacity, non-toxic and harmless characteristics, it is widely used in the field of catalysis, especially in NH 3 -SCR reaction and Hg 0It has attracted much attention in the removal of mercury. Fe doping can significantly increase the number of defects on the catalyst surface, promote the free migration of oxygen, generate more lattice oxygen and oxygen vacancies, and thus improve the redox ability of the catalyst. More importantly, the Fe-O-Mn dual active center that may be formed in the Fe-OMS-2 system not only changes the coordination environment of manganese ore, but also significantly enhances the redox ability of the catalyst active site, further improving the catalytic performance of OMS-2. This synergistic effect greatly improves the catalytic performance of OMS-2, and it performs well in the oxidation and denitration of elemental mercury. Although acid etching modification combined with the introduction of iron-based catalysts has significantly improved the catalytic performance of OMS-2, its reduction performance still has room for further improvement under low temperature conditions. Sodium borohydride, as a strong reducing agent, can reduce some high-valent metal ions on the catalyst surface, balance the redox performance of the material, and may promote the formation of more active sites. It is possible to improve the denitration performance of the catalyst while maintaining its excellent mercury oxidation performance. However, in the face of steel sintering flue gas with complex components, the stability of the catalyst needs to be further improved. Studies have shown that silica as a shell can improve the overall stability of the catalyst, increase the exposure of active sites, thereby improving the catalytic efficiency and the stability of the catalyst. In addition, the good thermal stability of silica makes it suitable for reactions under high temperature conditions, and it can act as a barrier to reduce the poisoning of toxic substances to the catalyst and extend its service life. This strategy is expected to achieve NO and Hg removal in sintering flue gas by natural cryptomelane catalysts. 0 It provides new ideas for efficient collaborative control.

[0005] In summary, the preparation method of acid etching, iron oxide modification and sodium borohydride reduction and simultaneous coating of silicon dioxide shell layer proposed in the present invention has opened up a new way for application in the field of denitrification and demercuration of steel sintering flue gas in non-electric industry. The catalyst not only has excellent catalytic performance, but also shows good economic and environmental protection, and has broad market prospects and application value. Summary of the invention

[0006] For the above-mentioned low-temperature selective catalytic reduction of NO and simultaneous catalytic oxidation of Hg 0 The present invention provides a method for simultaneously removing nitric oxide (NO) and mercury (Hg 0 ) catalyst and its preparation method.

[0007] In order to achieve the above object, the technical solution provided by the present invention is:

[0008] A Fe-OMS-2@SiO2 for simultaneous low-temperature removal of mercuric nitrate 2 Core-shell catalyst, the catalyst is composed of transition metal Fe 2 O 3 The composite material of modified OMS-2 is used as the core, with SiO2 The catalyst is denoted as Fe-OMS-2@SiO 2 .

[0009] Furthermore, the catalyst is composed of the following compositions in percentage by mass:

[0010] Fe 2 O 3 : 9% to 20% (more preferably 10% to 15%), SiO 2 : 12% to 28% (more preferably 17% to 26%), the remainder is OMS-2, and the sum of the mass percentages of the three components is 100%.

[0011] Furthermore, the catalyst has a rich pore structure, and its specific surface area, total pore volume and average pore diameter are 60-85m 2 / g, 0.1~0.4cm 3 / g, 10~20nm.

[0012] The above-mentioned Fe-OMS-2@SiO 2 A method for preparing a catalyst, the method comprising the following steps:

[0013] (1) OMS-2 and citric acid are mixed at a constant temperature by a condensation reflux method, citric acid etching is performed, and then dried to obtain a citric acid etched OMS-2 material, which is recorded as N-OMS-2;

[0014] (2) A certain amount of N-OMS-2 material was weighed and added to the ferric nitrate precursor solution, and then the mixture was subjected to hydrothermal reaction, drying and calcination to prepare Fe 2 O 3 Modified OMS-2 solid material;

[0015] (3) The Fe synthesized in step (2) 2 O 3 The modified OMS-2 solid material is reduced with sodium borohydride to obtain the material Fe-OMS-2;

[0016] (4) Using the Fe-OMS-2 material prepared in steps (1) to (3) as the core, a layer of SiO is uniformly impregnated on the surface of the Fe-OMS-2 using CTAB-assisted stirring impregnation. 2 shell, and obtain the core-shell structure Fe-OMS-2@SiO 2 catalyst.

[0017] Furthermore, the specific preparation method of the N-OMS-2 in step (1) is: weigh 3-8 g of OMS-2 and 100-200 mL (0.01-0.03 ml / mol) of citric acid solution and mix them at a reflux temperature of 70±1° C., and the reaction time is 20-30 min. The obtained sample is filtered and dried at 40-80° C. for 10-16 h to obtain the N-OMS-2 material.

[0018] Further, the hydrothermal reaction in step (2) is to react N-OMS-2 and a precursor solution in a reactor; wherein the precursor solution is obtained by mixing 2 to 3 g of ferric nitrate nonahydrate and 30 to 80 ml of deionized water; the amount of N-OMS-2 is 3 to 8 g; N-OMS-2 and the precursor solution are reacted in a reactor at 150 to 200 ° C for 18 to 30 hours, filtered and washed, and then dried at 100 to 120 ° C for 10 to 20 hours, and finally the dried solid material is placed in a muffle furnace for calcination, from room temperature to 300 to 400 ° C and maintained for 3 to 4 hours, the heating rate is 1 to 5 ° C / min, and finally cooled to room temperature to obtain Fe 2 O 3 Modified OMS-2 solid material.

[0019] Furthermore, step (3) is specifically as follows:

[0020] Sodium borohydride solution was slowly added to Fe 2 O 3 The mixed solution of the modified OMS-2 solid material is mixed and stirred for 6 to 12 hours, and a filter cake is obtained after filtration and elution with a Buchner funnel. The filter cake is dried in an oven at 100 to 120° C. for 10 to 20 hours to obtain Fe-OMS-2 material; wherein Fe 2 O 3 The mixed solution of the modified OMS-2 solid material is 1-4 g Fe 2 O 3 The modified OMS-2 solid material is obtained by stirring in 20-70 ml ultrapure water for 10-30 minutes; the sodium borohydride solution is obtained by mixing 0.5-1.2 g of sodium borohydride and 50-100 ml of deionized water.

[0021] Furthermore, step (4) is specifically as follows:

[0022] Weigh 0.2-0.7g Fe-OMS-2 material, transfer it to a beaker, add 30-60ml ethanol and 100-150ml ultrapure water in sequence, mix the beaker ultrasonically for 5-12min, add 0.2-0.5g CTAB, 2-3ml ammonia water, and 0.2-0.5ml tetraethyl orthosilicate (TEOS) to the mixed solution, stir at 20-50°C for 6-10h, wash with anhydrous ethanol and ultrapure water after centrifugation, dry in an oven at 40-100°C for 10-20h, and then place the dried solid in a muffle furnace for calcination, heating from room temperature to 300-400°C and maintaining for 3-4h, with a heating rate of 1-5°C / min, and finally cooling to room temperature to obtain Fe-OMS-2@SiO 2 catalyst.

[0023] The present invention will be further described below:

[0024] The present invention focuses on developing an efficient and economical core-shell catalyst Fe-OMS-2@SiO 2 The catalyst has a unique pore structure (both macropores and mesopores) and optimized surface chemical properties through a carefully designed preparation process (including citric acid etching, hydrothermal synthesis, sodium borohydride treatment and shell coating), which is designed to target NO and Hg in flue gas from non-electrical industries (such as steel sintering, etc.). 0 Emissions are effectively controlled.

[0025] The technical effects and application prospects of the present invention are:

[0026] By finely regulating the pore structure and surface chemical properties of the catalyst, the Fe-OMS-2@SiO 2 Core-shell catalysts can achieve efficient NO selective catalytic reduction and Hg 0 Catalytic oxidation meets the strict requirements of non-electric industry for steel sintering flue gas treatment. Using cheap and readily available natural cryptomelane as raw material, a high-performance catalyst is prepared through a simple modification method, which greatly reduces the production cost. It avoids the environmental pollution problems that may be caused by traditional V-based catalysts and conforms to the development trend of green chemistry. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Example 4 for Fe-OMS-2@SiO 2 Scanning electron microscopy image of the catalyst.

[0028] Figure 2 Example 4 for Fe-OMS-2@SiO 2 Catalyst adsorption-desorption test curve.

[0029] Figure 3The Fe-OMS-2@SiO 2 Catalyst pore size distribution test results.

[0030] Figure 4 For Example 5, Fe-OMS-2@SiO 2 XRD test spectrum of catalyst. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below with reference to specific embodiments, but the present invention is not limited thereto.

[0032] Example 1

[0033] The specific preparation method of N-OMS-2 is as follows:

[0034] 5 g of OMS-2 and 0.288 g of citric acid were weighed and mixed in 150 mL of ultrapure water to prepare a 0.01 mol / L citric acid solution, which was refluxed at 70°C for 30 minutes. The obtained sample was filtered, washed with deionized water until neutral, and dried at 60°C overnight to obtain the final product.

[0035] Example 2

[0036] The Fe-OMS-2@SiO 2 The preparation method of the catalyst comprises the following steps:

[0037] (1) 2.069 g Fe(NO 3 ) 3 9H 2 O was dissolved in 50 ml of ultrapure water and stirred at 25 °C for 15 min to prepare a precursor solution;

[0038] (2) adding 2 g of N-OMS-2 to the precursor solution prepared in step (1), stirring at 25° C. for 1 h, and then transferring to a polytetrafluoroethylene liner, placing in a high-pressure reactor, reacting at 180° C. for 24 h, washing the filtered material thoroughly after cooling, drying in an oven at 105° C. for 12 h after rinsing, and calcining the dried solid in a muffle furnace, heating from room temperature to 350° C. and maintaining for 4 h, with a heating rate of 3° C. / min, and cooling to room temperature to obtain an intermediate solid material;

[0039] (3) Weigh 2 g of the solid material prepared in step (2) and add it to 50 ml of ultrapure water to prepare solution A, stir at 25°C for 1 h, weigh 0.9728 g of sodium borohydride and add it to 65 ml of ultrapure water to prepare sodium borohydride solution B, slowly add solution B dropwise to solution A, mix and stir at 25°C for 10 h, filter and wash with a Buchner funnel, put the filter cake into an oven and bake at 105°C for 12 h, and then cool to room temperature to obtain the xFe-OMS-2 catalyst.

[0040] (4) 0.5 g of Fe-OMS-2 material was added to 40 ml of ethanol and 110 ml of ultrapure water for ultrasonic mixing for 10 min. 0.2 g of CTAB, 2.8 ml of ammonia water, and 0.47 ml of TEOS were added to the solution and stirred at 35 °C for 6 h. After centrifugation, it was washed with anhydrous ethanol and ultrapure water and filtered. It was dried in an oven at 60 °C for 12 h. The dried solid was calcined in a muffle furnace from room temperature to 350 °C and maintained for 4 h at a heating rate of 3 °C / min. Finally, it was cooled to room temperature to obtain Fe-OMS-2@SiO 2 Catalyst: Pass the catalyst through a 60-80 mesh sieve for later use.

[0041] Example 3

[0042] The catalyst prepared by the present invention is used to catalyze the reduction of NO and the simultaneous oxidation of Hg 0 performance.

[0043] Fe-OMS-2@SiO prepared in Example 2 of the present invention 2 The catalyst was the experimental object. 0.3 g of catalyst was loaded into the catalytic reactor, the total gas flow rate was 200 ml / min, and the gas composition was: 16 vol% O 2 , 500ppmNO, 500ppmNH 3 , 80 μg / m 3 Hg 0 , balance gas N 2 ; airspeed is 50000h -1 The reaction temperature was controlled at 50-300°C, and the catalyst was tested for catalytic reduction of NO and simultaneous oxidation of Hg 0 performance.

[0044] Example 4

[0045] SEM and BET tests of the catalyst of the present invention.

[0046] In the present invention, the morphology and structure of the catalyst were photographed using a MIRA3 LMU (TESCAN) field emission scanning electron microscope system. The specific surface area and pore structure analysis were both measured using a Micromeritics Tristar ΙΙ3020 from Quantachrom, USA. Taking the test results of the product obtained in Example 2 as an example, the test results are as follows: Figure 1 , Figure 2 and Figure 3 As shown, the results showed that Fe 2 O 3 The silica microspheres were evenly dispersed on the surface of OMS-2. The results showed that the xFe-OMS-2@SiO2 The catalyst has a macroporous mesoporous structure with a surface area of ​​70.80 m 2 / g, and the total pore volume is 0.216cm 3 / g, and the average pore size is 12.19nm.

[0047] Example 5

[0048] XRD test of the catalyst of the present invention.

[0049] The physical structure of the catalyst in the present invention was analyzed and characterized by a Rigaku rotaflex D / MAX-2500 / pc X-ray diffractometer of Hitachi, Japan. The test conditions were Cu target Ka ray (λ=1.5406A), scanning 2θ range 5-80°, scanning speed 10° / min, and the test results were as follows: Figure 4 The results show that a group of pyrolusite MnO 2 (PDF#81-2261) matches the diffraction peak at 22.6°, which is the presence of quartz SiO 2 (PDF#46-1045) and a group of weak peaks related to hematite Fe 2 O 3 (PDF#89-0596) matches the diffraction peaks, indicating that Fe 2 O 3 Exists in highly dispersed very small crystalline phase.

[0050] The results show that the Fe-OMS-2@SiO 2 Core-shell catalysts have rich pore structures, which can promote the dispersion of active components, expose more active sites, improve electron transfer and redox capabilities, and enrich surface acid sites, thereby enabling efficient removal of NO and Hg 0 .

Claims

1. A Fe-OMS-2@SiO2 core-shell catalyst for low-temperature synergistic denitrification and demercuration, characterized in that: The Fe-OMS-2@SiO2 core-shell catalyst comprises a Fe-OMS-2 core formed by Fe2O3 loaded on OMS-2 natural cryptomelane and a SiO2 shell impregnated on the surface of the Fe-OMS-2 core by CTAB-assisted stirring.

2. The catalyst according to claim 1, characterized in that The mass percentage contents of Fe2O3, SiO2 and OMS-2 in the catalyst are as follows: Fe2O3 is 9% to 20%, SiO2 is 12% to 28%, and the rest is OMS-2, and the sum of the mass percentages of the three components is 100%.

3. The Fe-OMS-2@SiO2 catalyst for simultaneous removal of mercuric nitrate according to claim 1, characterized in that: The catalyst has a rich pore structure, and its specific surface area, total pore volume and average pore diameter are 60-85 m 2 / g, 0.1~0.4cm 3 / g, 10~20nm.

4. The method for preparing the Fe-OMS-2@SiO2 catalyst for low-temperature synergistic removal of mercuric nitrate according to claims 1 to 3, characterized in that: The method comprises the following steps: (1) OMS-2 and citric acid are mixed under constant temperature conditions by condensation reflux, citric acid etching is performed, and citric acid etching OMS-2 material is obtained by drying, which is recorded as N-OMS-2; (2) Weighing a certain amount of N-OMS-2 material, adding it to the iron nitrate precursor solution, mixing it, and then performing hydrothermal reaction, drying and calcining to prepare Fe2O3-modified OMS-2 solid material; (3) reducing the Fe2O3-modified OMS-2 solid material synthesized in step (2) with sodium borohydride to obtain a material Fe-OMS-2; (4) Using the Fe-OMS-2 material prepared in steps (1) to (3) as the core, a layer of SiO2 shell is uniformly impregnated on the surface of Fe-OMS-2 using CTAB-assisted stirring to obtain a core-shell structured Fe-OMS-2@SiO2 catalyst.

5. The method according to claim 4, characterized in that The specific preparation method of N-OMS-2 in step (1) is as follows: weigh 3-8 g of OMS-2 and 100-200 mL (0.01-0.03 ml / mol) of citric acid solution and mix them at a reflux temperature of 70±1° C. The reaction time is 20-30 min, the sample is filtered, and dried at 40-80° C. for 10-16 h to obtain the N-OMS-2 material.

6. The preparation method according to claim 4, characterized in that: The hydrothermal reaction in step (2) is to react N-OMS-2 and a precursor solution in a reactor; wherein the precursor solution is obtained by mixing 2 to 3 g of ferric nitrate nonahydrate and 30 to 80 ml of deionized water; the amount of N-OMS-2 used is 3 to 8 g; N-OMS-2 and the precursor solution are reacted in a reactor at 150 to 200° C. for 18 to 30 hours, filtered and washed, and then dried at 100 to 120° C. for 10 to 20 hours, and finally the dried solid material is placed in a muffle furnace for calcination, rising from room temperature to 300 to 400° C. and maintained for 3 to 4 hours, with a heating rate of 1 to 5° C. / min, and finally cooled to room temperature to obtain Fe2O3-modified OMS-2 solid material.

7. The preparation method according to claim 4, characterized in that: The sodium borohydride reduction described in step (3) is specifically as follows: slowly adding the sodium borohydride solution dropwise into the mixed solution of the Fe2O3-modified OMS-2 solid material, mixing and stirring for 6 to 12 hours, filtering and eluting with a Buchner funnel to obtain a filter cake, and drying the filter cake in an oven at 100 to 120°C for 10 to 20 hours to obtain the Fe-OMS-2 material; wherein the mixed solution of the Fe2O3-modified OMS-2 solid material is obtained by stirring 1 to 4 g of the Fe2O3-modified OMS-2 solid material in 20 to 70 ml of ultrapure water for 10 to 30 minutes; and the sodium borohydride solution is obtained by mixing 0.5 to 1.2 g of sodium borohydride and 50 to 100 ml of deionized water.

8. The preparation method according to claim 4, characterized in that: Step (4) is specifically as follows: weigh 0.2-0.7 g of Fe-OMS-2 material, transfer it to a beaker, add 30-60 ml of ethanol and 100-150 ml of ultrapure water in sequence, ultrasonically mix the beaker for 5-12 min, add 0.2-0.5 g of CTAB, 2-3 ml of ammonia water, and 0.2-0.5 ml of tetraethyl orthosilicate (TEOS) to the mixed solution, respectively, and stir at 20-50° C. for 6-10 h. After centrifugation, wash and filter with anhydrous ethanol and ultrapure water, dry in an oven at 40-100° C. for 10-20 h, then place the dried solid in a muffle furnace for calcination, raise the temperature from room temperature to 300-400° C. and maintain for 3-4 h, with a heating rate of 1-5° C. / min, and finally cool to room temperature to obtain a Fe-OMS-2@SiO2 catalyst.

Citation Information

Cited By

  • Manganese-potassium hidden ore-based core-shell catalyst for synergistically removing NOx and VOCs at medium and low temperatures as well as preparation method and application of manganese-potassium hidden ore-based core-shell catalyst

    CN121060552A